2009
DOI: 10.1111/j.1740-0929.2009.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary ratios of corn silage and alfalfa hay on carbohydrate digestion and retention time of feed particles in the gastrointestinal tract of steers

Abstract: Four Holstein steers fitted with duodenal cannula were used in a 4 x 4 Latin square design to investigate the effect of the combination of corn silage (CS) and alfalfa hay (AH) in different ratios on the ruminal and intestinal digestion of carbohydrates and feed particle passage rate. Steers were fed mixed diets containing both CS and AH in ratios of 80:20, 60:40, 40:60 and 20:80 on a dry matter basis at 95% of ad libitum feed intake. The increase of AH proportion in diets increased dry matter intake and rumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…; Obitsu et al . ). Furthermore, as an extrinsic factor, slightly lower pH at 6 h after feeding for the CSP diets may have reduced the population of ruminal fibrolytic bacteria and their attachment to feed particles (Wanapat et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Obitsu et al . ). Furthermore, as an extrinsic factor, slightly lower pH at 6 h after feeding for the CSP diets may have reduced the population of ruminal fibrolytic bacteria and their attachment to feed particles (Wanapat et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, Obitsu et al . () showed a decreased ruminal passage rate for both CS and alfalfa hay particles and also an increased ruminal NDF digestibility when dietary chopped alfalfa hay proportion in the CS‐based diet increased from 20% to 60% in steers.…”
Section: Discussionmentioning
confidence: 98%
“…The results in the current experiment indicate that the observations presented in previous reports might not result from a decreased CS passage rate due to grass hay or silage addition. However, Obitsu et al (2009) showed a decreased ruminal passage rate for both CS and alfalfa hay particles and also an increased ruminal NDF digestibility when dietary chopped alfalfa hay proportion in the CS-based diet increased from 20% to 60% in steers. However, Obitsu et al (2009) showed a decreased ruminal passage rate for both CS and alfalfa hay particles and also an increased ruminal NDF digestibility when dietary chopped alfalfa hay proportion in the CS-based diet increased from 20% to 60% in steers.…”
Section: Digestibility and Ruminal Passage Ratesmentioning
confidence: 91%
See 1 more Smart Citation